Chemical and Physical Characteristics of Cooking Oil After Tempeh Frying - Sri Hartati Afriyanti; Catur Budi Handayani; Catur Budi Handayani; Cindhe Putri Larasati (Universitas PGRI Semarang, 2019)
This study aims to determine the effect of seasoning and type of oil on chemical and physical characteristics of cooking oil after being used for tempeh frying. This factor needs to be learned to understand how to handle it. The experimental design used in this study was a factorial completely randomized design with two treatments, namely, (A) Seasoning consisting of (A1) No Seasoning and (A2) Seasoning. The second treatment is the type of oil (B) consisting of: (B1) bulk oil, (B2) GM oil, (B3) Sunco oil. The experiment was repeated 3 times so that 18 experimental units were obtained. The parameters measured were free fatty acid levels, oil color and water content. The results showed that seasoning and type of oil affect the levels of free fatty acids, oil color and water content. The highest free fatty acid levels were obtained from seasoned tempe frying using bulk oil of 1.53%. The yellowest oil color and the highest water content obtained from seasoning tempeh frying using bulk oil of 32.07 and 0,06%.